Internalisasi Nilai-Nilai Living Quran Di Pondok Pesantren Roudhotul Quran Tlogo Anyar Lamongan - Yunus, Muhamad (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Abstrack:The living Koran refers to the real understanding and experience of the Koran in everyday life. This article emphasizes the importance of actively interacting with the Al-Quran, understanding its meaning, and applying its values ​​in daily life. Roudhotul Quran Islamic Boarding School focuses on teaching the Koran and instilling Islamic values ​​in its students. The implementation of the Al-Quran that lives in this Islamic boarding school includes Al-Quran education, the practice of Al-Quran values, Islamic character education, religious activities, and creating an environment that is in line with religious understanding in everyday life. This article highlights the relevance of the teachings of the Koran in modern times and the importance of character education based on the Koran. Internalization of the living values ​​of the Koran is important for implementing the teachings of the Koran in everyday life. The Quran provides guidance for various aspects of human life, including the relationship with Allah, with fellow human beings, and with the universe. In order to internalize these values, educators must understand the holistic nature of human beings and approach their teaching in a comprehensive manner. The Roudhotul Quran Islamic Boarding School in Tlogo Anyar Lamongan, Indonesia, applies a living Quranic approach to educating its students and promoting Quranic values ​​in their daily lives. Data for this study were collected through observation, interviews, and documentation. The findings from this study will contribute to an understanding of how the Al-Quran living approach can be implemented effectively in educational institutions. Keywords: internalization of values, Living Qur’an. Abstrak. Al-Quran yang hidup mengacu pada pemahaman dan pengalaman nyata Al-Quran dalam kehidupan sehari-hari. Artikel ini menekankan pentingnya berinteraksi aktif dengan Al-Quran, memahami maknanya, dan menerapkan nilai-nilainya dalam kehidupan sehari-hari. Pondok Pesantren Roudhotul Quran fokus pada pengajaran Al-Quran dan penanaman nilai-nilai Islam pada santrinya. Implementasi Al-Quran yang hidup di pesantren ini meliputi pendidikan Al-Quran, pengamalan nilai-nilai Al-Quran, pendidikan akhlak Islami, kegiatan keagamaan, dan menciptakan lingkungan yang sejalan dengan pemahaman agama dalam kehidupan sehari-hari. Artikel ini menyoroti relevansi ajaran Alquran di zaman modern dan pentingnya pendidikan karakter berdasarkan Alquran. Internalisasi nilai-nilai hidup Al-Quran penting untuk mengimplementasikan ajaran Al-Quran dalam kehidupan sehari-hari. Al-Qur'an memberikan petunjuk dalam berbagai aspek kehidupan manusia, termasuk hubungan dengan Allah, dengan sesama manusia, dan dengan alam semesta. Untuk menginternalisasikan nilai-nilai tersebut, pendidik harus memahami sifat holistik manusia dan melakukan pendekatan pengajarannya secara komprehensif. Pondok Pesantren Roudhotul Quran di Tlogo Anyar Lamongan, Indonesia, menerapkan pendekatan Al-Quran yang hidup dalam mendidik santrinya dan menyebarkan nilai-nilai Al-Quran dalam kehidupan sehari-hari. Data untuk penelitian ini dikumpulkan melalui observasi, wawancara, dan dokumentasi. Temuan penelitian ini akan memberikan kontribusi pada pemahaman bagaimana pendekatan penghidupan Al-Quran dapat diterapkan secara efektif di lembaga pendidikan. Kata Kunci: internalisasi nilai, Living Quran.